Pigeonpea Ratooning Trial Under Conservation Agriculture - International Maize and Wheat Improvement Center; Zambian Agriculture Research Institute (International Food Policy Research Institute, 2019)
This study contains data generated from the on-station trial that was conducted to evaluate the various management methods that are being advocated in the region. The following treatments were used for this trial. - Sole maize continuous; - Full Pigeonpea/maize rotation - Maize + Pigeonpea full growth no ratooning; - Maize + Pigeonpea, uprooting at harvest and re-seeding every year; - Maize + Pigeonpea, ratooning at harvest and at seeding;- Maize + Pigeonpea, ratooning at harvest and 2 weeks after maize seeding; - Maize + Pigeonpea, ratooning at harvest and 3 weeks after maize seeding; - Maize + cut Pigeonpea from last season at ground level 2 weeks after maize planting and reseed; - Maize + delay planting of maize by a minimum of 14 days, cut Pigeonpea at base, reseed Pigeonpea with maize 14 days after the planting window.